Modeling δD-δ18O Steady-State of Well-Sealed Perennially Ice-Covered Lakes and Their Recharge Source: Examples From Lake Untersee and Lake Vostok, Antarctica - Faucher, Benoit; Lacelle, Denis; Fisher, David A.; Weisleitner, Klemens; Andersen, Dale T. (Frontiers in Earth Science, 2020)
Perennially ice-covered lakes that are tightly sealed from the atmosphere represent a unique group of polar lakes. In these lakes, the δD-δ18O evolution of the water column and steady-state conditions are controlled by rates of recharge and freezing at the bottom of the ice cover. We developed a recursive model (FREEZCH9) that takes into account the changing salinity in the water column as a result of freezing and mixes the recharge water to the residual water in well-sealed perennially ice-covered lakes. Our model is tested against datasets from Lake Vostok and is used to assess the δD-δ18O mass balance of Lake Untersee and evaluate if the lake is in isotopic steady-state. Our FREEZCH9 simulations fit well with the predicted δD-δ18O values of Lake Vostok’s upper water column and the overlying accreted ice. Simulations with FREEZCH9 also suggests that Lake Untersee is in isotopic steady-state and that its two input sources (i.e., subaqueous terminus melting of the Anuchin Glacier and subglacial meltwater) have similar δD-δ18O composition. Our modeling demonstrates that Lake Untersee most likely did not receive additional input from surface streams during the last 300–500 years. FREEZCH9 may be also used to determine if any groundwater systems of the McMurdo Dry Valleys are fully or partially recharged by subglacial lakes.